Addition of Crop Residues with Different C:N Ratios on the Release Pattern of Available Nitrogen and Sulfur in Different Soils. Issue 22 (16th December 2021) - Singh, Sreejan; Sharma, P. K.; Singh, Surendra; Kumar, Arvind
ABSTRACT: Mineralization of organic N and S of crop residue is an important useful tool for forecasting availability of N and S in soils. Three different soils (Vertisol, Inceptisol and Alfisol) from eastern Uttar Pradesh, India; seven crops residue, four cereals (rice, barley, maize, wheat) from irrigated area of Varanasi; and three pulses (gram lentil, pigeon pea) from rainfed area of Mirzapur were used in 90-day incubation study under controlled condition to estimate the release of soil available N and S. The experiment was laid out in a factorial completely randomized design with three replications. Total Nitrogen (N) and total Sulfur (S) contents were higher in the pulses than that of cereals. Pulses residue with the lowest C:N:S ratio (177.0:3.7:1 to 195.8:4.5:1) had significantly rapid rate of N and S release up to 45 days and then declined at 60 and 90 days. On the other hand, cereals with the highest C:N:S ratio (390.8:4.3:1 to 463.6:5.0:1) had slow release of N and S up to 45 days and then rapid released at 60 and 90 days. Among pulses residue, pigeon pea has resulted significantly higher net release of soil available N and S at day 45 to the extent of 18.4 and 78.7% in Alfisol, 17.7 and 51.2% in Inceptisol, and 15.0 and 24.1% in Vertisol, respectively, over control. Among the cereals residue, barley residue amended Alfisol had higher net increase in available N at day 90 (13.2%) followed by Inceptisol (10.8%) and Vertisol (9.9%) over control.